Genetic influence on the kinetics and associated pathology of the early stage (intestinal-hepatic) migration of Ascaris suum in mice - HOLLAND, CELIA; STAFFORD, PETER (My University, 2010)
The generative mechanism(s) of aggregation and predisposition to Ascaris lumbricoides and A. suum infections in their host population are currently unknown and difficult to elucidate in humans and pigs for ethical/logistical reasons. A recently developed, optimized murine model based on 2 inbred strains, putatively susceptible (C57BL/6j) and resistant (CBA/Ca) to infection, was exploited to elucidate further the basis of the contrasting parasite burdens, most evident at the pulmonary stage. We explored the kinetics of early infection, focusing on the composite lobes of the liver and lung, over the first 8 days in an effort to achieve a more detailed understanding of the larval dispersal over time and the point at which worm burdens diverge. Larval recoveries showed a heterogenous distribution among the lobes of the lungs, being higher in the right lung of both strains, and in the susceptible strain larvae accumulating preferentially in 2 (caudal and middle) of the 4 lobes. Total larval burdens in these 2 lobes were largely responsible for the higher worm burdens in the susceptible strain. While total lung larval recoveries significantly differed between mouse strains, a difference in liver larval burdens was not observed. However, an earlier intense inflammatory response coupled with more rapid tissue repair in the hepatic lobes was observed in CBA/Ca mice, in contrast to C57BL/6j mice, and it is possible that these processes are responsible for restricting onward pulmonary larval migration in the resistant genotype.
PUBLISHED
Keywords: Ascaris lumbricoides; Infectious Diseases; Ascaris suum; Immunology, Inflammation & Infection